A Historical Overview of Turkey's Animal Welfare Legislation - Ozen, Abdullah (Kafkas Univ, Veteriner Fakultesi Dergisi, 2017)
There were a number of legal codes which aimed to protect animal welfare in Turkish history, but there was no separate animal welfare law until 2004. Although Animal Protection Law (5199) had been accepted on July 01, 2004, little progress had been shown until 2010, except for Regulation on the Protection of Experimental Animals Used for Experimental and Other Scientific Purposes and the Procedures and Principles of the Establishment, Operation and Inspection of Experimental Animal Production Premises and Laboratories Performing Animal Experiments, Regulation on the Procedures and Principles of the Work of Zoos and Implementing Regulation on Animal Protection. The framework of the adhesion process to the EU the regulation has been made under Law No. 5996 on June 13, 2010 and it has a separate animal welfare article. After this law went into effect, two new regulations were issued on December 23, 2011: The Regulation on welfare of Farm Animals and, The Regulation on the Welfare and Protection of Animals during Transport. But, at the end of the 2014, The Regulation on welfare of Farm Animals was issued and former one repealed. All these legislations are quite similar to the EU's regulations. However, there were no subject specific legislations on slaughtering and any species-specific stipulations except for welfare standards for the protection of calves and laying hens.
Türkiye’de hayvan refahı mevzuatına tarihsel bir bakış
Keywords: Animal protection; Animal welfare; Legislation; Turkey